Italians in Lisbon´'s neighbourhoods (17th century) - Alessandrini, Nunziatella (2015)
This paper is meant to be regarded as the next stage of an earlier work of ours on the Italian presence in Sixteenthcentury Lisbon neighborhoods. From the early decades of the 1500s Lisbon began to expand along its riverside towards West, even though its walls still marked the city limits until the 1755 Earthquake. The primitive Italian residence will also be affected by this urban expansion. It is true that core mercantile areas of the City such as the rua Nova dos Mercadores and São Julião’s parish in general still remained as the Italians preferential choices for their residence. However, after the construction of Loreto’s church in 1518 and São Roque in 1569, Italian merchants changed their preferences, looking for housing opportunities closer to the so-called igreja dos Italianos, and afterwards to the quarters of São Paulo and Corpo Santo.